Processes of formation of micro -and nanodispersed systems - Bochkarev, A A. (CRC Press, 2016)
"The disperse system is a set of individual elements of material with the characteristic dimensions considerably smaller than the dimensions of the system as a whole. The disperse medium is the medium consisting of the individual elements of the material of one phase, separated from each other by the material of the other phase. The disperse system or medium is microdisperse if the total surface area of its disperse elements influences the macroscopic properties of the material, forming the system or medium. The microdisperse system or medium is nanodisperse if the elements forming it are so small that their molecular properties greatly influence the properties of the system or medium as a whole and even lead to the formation of new properties which the homogeneous matter does not have. The new properties of the disperse systems make it possible to develop and create new technologies which are referred to as nanotechnologies. The process as a result of which the material is transformed from the homogeneous to the disperse state is referred to as dispersion. As a result of dispersion the individual elements of the matter of the produced disperse system are separated by the interlayers of a foreign medium. In the process of refining the matter the increase of the number N of the individual elements with the size r in the closed system the total area of the boundaries of the matter S with the foreign medium increase in inverse proportion to the size of the elements S ~ r-1 and in proportion to the cubic root of the number of the elements S ~ N1/3"--